2021
DOI: 10.1002/hbm.25588
|View full text |Cite
|
Sign up to set email alerts
|

Network properties and regional brain morphology of the insular cortex correlate with individual pain thresholds

Abstract: Pain thresholds vary considerably across individuals and are influenced by a number of behavioral, genetic and neurobiological factors. However, the neurobiological underpinnings that account for individual differences remain to be fully elucidated. In this study, we used voxel-based morphometry (VBM) and graph theory, specifically the local clustering coefficient (CC) based on resting-state connectivity, to identify brain regions, where regional gray matter volume and network properties predicted individual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…Moreover, in their aforementioned study, Grant et al reported a negative association between cortical thickness and pain sensitivity in long-term mediation practitioners not only in the rACC, but interestingly, also in the PHG (Grant et al, 2010). Neumann et al recently also reported increased grey matter volume in PHG with lower pain sensitivity (Neumann et al, 2021) in center 1 of the present multi-center analysis.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, in their aforementioned study, Grant et al reported a negative association between cortical thickness and pain sensitivity in long-term mediation practitioners not only in the rACC, but interestingly, also in the PHG (Grant et al, 2010). Neumann et al recently also reported increased grey matter volume in PHG with lower pain sensitivity (Neumann et al, 2021) in center 1 of the present multi-center analysis.…”
Section: Discussionsupporting
confidence: 65%
“…Although we still lack a rigorously validated structure-based predictive model for pain sensitivity, several studies have reported structural brain correlates of the sensitivity to pain on the group level. Voxel-based morphometry (VBM) studies have reported that pain sensitivity is significantly correlated to structures including the cingulate cortex (CC), precuneus, primary somatosensory cortex (S1), putamen, insula, parahippocampal gyrus (PHG), among others (Emerson et al, 2014; Neumann et al, 2021; Niddam et al, 2021; Ruscheweyh et al, 2018; Zhang et al, 2020). Surface based morphometry techniques (Fischl, 2012) can provide additional insights and, in contrast to VBM, a better account for gyrification via measures such as parcellated brain cortical thicknesses and volumes (Fischl et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The anterior insula connects to prefrontal and anterior cingulate cortices, which are implicated in cognitive pain modulation 15 , 23 , and these connections were shown to be important features in predicting individual pain sensitivity 17 . Additionally, in our recent study we found that morphological and functional network properties of the posterior insula are also associated with pain sensitivity 24 . Based on this, the anterior-dominant connectopy might represent a more effective connectivity layout in terms of top-down pain modulation.…”
Section: Discussionmentioning
confidence: 78%
“…Studies have reported the differences in nodal degree and PC of functional brain networks between patients with CBP and the HCs (72,73). The CC of the insular cortex was found to be correlated with individual pain thresholds (74). Therefore, the combination of the TGI of these three network properties can comprehensively depict the alternation of brain networks of patients with CBP, which undoubtedly performed better than the TGI of a single network property in predicting the pain intensity.…”
Section: Discussionmentioning
confidence: 99%